Academic socialization: on a neglected effect of competition in science - Hamann, Julian; Serrano-Velarde, Kathia (Higher education, 2024)
Competition is usually considered a mechanism for the allocation of scarce resources. This paper draws attention to a neglected effect of academic competition: competition provides participants with a normative orientation about field-specific values by informing them about which activities will be rewarded. We conceptualize this as a socializing effect. We study the socializing effects of competition for postdocs because this group is especially exposed to the dynamics of academic competition. Drawing on qualitative interviews with 60 postdocs in history and physics in Germany, the analysis reveals the orientations and values that competition conveys to postdocs. Since different forms of competition for publications, funding, and jobs are not neatly synchronized, they convey various expectations. Postdocs cope with this multiplicity, prioritizing a specific form of competition that is competition for funding. This comes at the expense of activities and tasks that are not organized competitively. The socializing effect of competition should be reflected more thoroughly not only by scholarship on academic competition but also by research policy that promotes competition.
Online veröffentlicht: 3. Oktober 2024
Gesehen am 26.02.2025